A industrialização da economia de Mato Grosso - Gonçalves, Heitor Tiago (2016)
This dissertation aims to advance the understanding of the industrialization of Mato Grosso economy historically positioned in primary export model. Begins with approach to the first steps on the processing of certain goods agropastoral origin. Advances with theoretical framework centered on David Ricardo, the dual models and ECLAC contributions. Then are estimated and analyzed indicators on the industrialization of Mato Grosso economy. These indicators are mainly represented by quantities of Industrial transformation, the decomposition of Industrial activity in Processing Industry and Industry Extractive, and the Gross Added Value by segment (Industry, Agriculture and Services), in the latter case, with cutout for each municipality . With adoption of analytical and descriptive methodology, formulated the following problem: There is an ongoing process of industrialization in the Mato Grosso economy? The hypothesis is that Mato Grosso economy still has low level of industrialization. The results obtained reveal that hypothesis must be rejected given that the model still ongoing in Mato Grosso economy based on agroindustrialization, viscerally connected to your primary base, mainly, producer and exporter of primary commodities, especially soybeans.